Model Pembelajaran Guided Inquiry di Era Merdeka Belajar: Efektivitas Projek Sains IPA Siswa di Sekolah Dasar - Hamna; Muh. Khaerul Ummah BK (Madako Elementary School, 2023)
Every learning activity that uses a model allows learning interactions between teachers and students, as well as between students and other students. The purpose of this study is to analyze the effectiveness of elementary school students' science learning projects in the Merdeka Belajar era through the implementation of guided inquiry learning. The research method is Quasi Experimental Design which does not require the sample to be randomly selected (random). This study involved all students at SD Negeri Kabinuang, with a sample of class V selected through a purposive mechanism. Written test instruments, direct observation, and documentation were used to collect data. Analyzed inferentially by using the results of processed statistical data. The results showed that the question-directed learning model is very effective in carrying out science projects in the Merdeka Belajar era. These results can be generalized in a broader context. The guided inquiry model is proven to be effective and appropriate to be applied in science learning based on science projects in elementary schools when used for science project activities that are in accordance with the desired learning concepts in the Merdeka Curriculum in elementary schools.